2018
DOI: 10.1186/s12933-018-0679-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between epicardial adipose tissue thickness and adipo-fibrokine indicator profiles post-myocardial infarction

Abstract: BackgroundDetermination of the impact of visceral obesity and epicardial adipose tissue thickness on stimulating growth factor levels during hospitalization for myocardial infarction is of potential importance for predicting outcomes and assessing the development of cardiofibrotic changes associated with maladaptive myocardial remodeling. In this study, we aimed to investigate the relationships between epicardial adipose tissue thickness, adipokine profiles, and the stimulating growth factor 2/interleukin-33 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 29 publications
1
26
0
1
Order By: Relevance
“…Previous studies have suggested that measurements of EFT are a substitute for visceral fat [8,9] EFT can secrete inflammatory factors, such as TNF-alpha, IL-6, adipocytokines, and leptin, via paracrine or endocrine activities [9,10] to locally regulate the myocardium and coronary artery function and regulate lipid and energy homeostasis in vivo. EFT has the ability to release and uptake free fatty acids and to affect low glucose utilization, which plays an important role in metabolic syndrome and coronary artery disease [11][12][13][14][15][16]. EFT can be measured by echocardiography, cardiac magnetic resonance imaging, and computed tomography (CT) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that measurements of EFT are a substitute for visceral fat [8,9] EFT can secrete inflammatory factors, such as TNF-alpha, IL-6, adipocytokines, and leptin, via paracrine or endocrine activities [9,10] to locally regulate the myocardium and coronary artery function and regulate lipid and energy homeostasis in vivo. EFT has the ability to release and uptake free fatty acids and to affect low glucose utilization, which plays an important role in metabolic syndrome and coronary artery disease [11][12][13][14][15][16]. EFT can be measured by echocardiography, cardiac magnetic resonance imaging, and computed tomography (CT) [17].…”
Section: Introductionmentioning
confidence: 99%
“…PVAT and EAT have the same embryological origin, and the increase in the size of either fat store is associated with the calcification of the coronary arteries [18,19], as well as the development of CAD [20]. Some researchers believe that an increase in the thickness of epicardial fat reflects the presence of visceral obesity in the body and serves as a prognostic marker of coronary heart disease and its associated complications [21]. The results obtained in this study show that EAT thickness is directly dependent on the value of the PVAT; this concurs with the results of previous studies [22,23].…”
Section: Methodsmentioning
confidence: 99%
“…Так, в ЭЖТ значительно более выраженная ýкспрессия IL-26, IL-1β, MCP-21, TNF-α и резистина по сравнению с подкожной жировой тканью [22]. Увеличение толщины ЭЖТ тесно связано с повышенным сердечно-сосудистым риском и уменьшением выделения адипокинов из ЭЖТ [23,24]. При наличии сердечно-сосудистых факторов риска, таких как ожирение, жировая ткань характеризуется повышенной инфильтрацией макрофагов, лимфоцитов и тучных клеток.…”
Section: связь эжт с развитием сердечно-сосудистой патологииunclassified